2016
DOI: 10.1093/hsw/hlw032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Racial and Socioeconomic Disparities on Binge Eating and Self-Efficacy among Adults in a Behavioral Weight Loss Trial

Abstract: The prevalence of obesity is a significant problem among racial and ethnic minorities and those of low socioeconomic status (SES). Psychosocial barriers, such as binge eating and low self-efficacy, are known to hinder the adoption of a more healthful diet. There is limited research identifying racial and SES differences in binge eating and self-efficacy. Further investigations of these constructs may allow researchers to improve the effectiveness of weight management interventions and increase social worker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…The results of study 2 provided further empirical support for the importance of examining the effect of SV on psychological outcomes among family caregivers of children with chronic diseases [5, 6, 24, 26, 46, 59–61]. The findings of study 2 are consistent with previous studies that reported a positive association between the duration of the child’s hospitalization and caregivers’ level of depression [5, 36, 43].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of study 2 provided further empirical support for the importance of examining the effect of SV on psychological outcomes among family caregivers of children with chronic diseases [5, 6, 24, 26, 46, 59–61]. The findings of study 2 are consistent with previous studies that reported a positive association between the duration of the child’s hospitalization and caregivers’ level of depression [5, 36, 43].…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, substantial theoretical, clinical and empirical evidence supports the relevance and representativeness of sociodemographic variables (SVs) in the health, human, and social sciences [25]. In particular, the literature on chronic disease has found important associations between the SV of children and their caregivers and negative health consequences in families [26]. Socioeconomic, cultural, environmental, and sociodemographic factors can thus interact with and determine an individual’s health status [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…For the population of patients seeking bariatric surgery, the recommendation based on the biopsychosocial theory included assessment, interventions, and measurable outcomes to demonstrate effectiveness. Goode et al (2016) cited self-efficacy deficits as key components contributing to obesity in the sample population and thereby evaluated the effectiveness of an intervention to empower the patient with education and assistance (Goode et al, 2016). In light of the evidence discussed, recommendations for the initial evaluation of the obese bariatric surgical patient include the full history and physical examination, as well as assessments of socioeconomic and health literacy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Average eating self-efficacy scores tend to be lower in studies of patients seeking bariatric surgery 9 than in non-surgical populations seeking behavioural weight loss. [10][11][12] Self-efficacy is also linked to future eating behaviours. 13 BED is consistently associated with reduced total eating self-efficacy in participants seeking behavioural weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Changing eating behaviours is facilitated by self‐efficacy, the extent that people believe they can make modifications 8 . Average eating self‐efficacy scores tend to be lower in studies of patients seeking bariatric surgery 9 than in non‐surgical populations seeking behavioural weight loss 10–12 . Self‐efficacy is also linked to future eating behaviours 13 .…”
Section: Introductionmentioning
confidence: 99%